Slave to habit? Obesity is associated with decreased behavioural sensitivity to reward devaluation. (1st April 2015) - Horstmann, Annette; Dietrich, Anja; Mathar, David; Pössel, Maria; Villringer, Arno; Neumann, Jane
Highlights: Dynamic change in motivational value promotes food seeking or meal cessation. Obese subjects ingest energy beyond their homeostatic needs. Adaptation of eating behaviour to change in motivational value possibly compromised. Implicit reward devaluation shows attenuated behavioural adjustment with higher BMI. Change in explicitly reported motivational value is not affected by BMI. Abstract: The motivational value of food is lower during satiety compared to fasting. Dynamic changes in motivational value promote food seeking or meal cessation. In obesity this mechanism might be compromised since obese subjects ingest energy beyond homeostatic needs. Thus, lower adaptation of eating behaviour with respect to changes in motivational value might cause food overconsumption in obesity. To test this hypothesis, we implemented a selective satiation procedure to investigate the relationship between obesity and the size of the behavioural devaluation effect in humans. Lean to obese men (mean age 25.9, range 19–30 years; mean BMI 29.1, range 19.2–45.1 kg/m 2 ) were trained on a free operant paradigm and learned to associate cues with the possibility to win different food rewards by pressing a button. After the initial training phase, one of the rewards was devalued by consumption. Response rates for and wanting of the different rewards were measured pre and post devaluation. Behavioural sensitivity to reward devaluation, measured as the magnitude of difference between pre and post responses, was regressed against BMI. Results indicate that (1) higher BMI compared to lower BMI in men led to an attenuated behavioural adjustment to reward devaluation, and (2) the decrease in motivational value was associated with the decrease in response rate between pre and post . Change in explicitly reported motivational value, however, was not affected by BMI. Thus, we conclude that high BMI in men is associated with lower behavioural adaptation with respect to changes in motivational value of food, possibly resulting in automatic overeating patterns that are hard to control in daily life.